Perancangan Sistem Informasi Berbasis Web untuk Objek Pariwisata di Kabupaten Pinrang - Zulvita; Sanatang Sanatang; Abdul Wahid (Sakura Publisher, 2024)
This research aims to produce a web-based Information System website for tourism objects in Pinrang Regency and determine the results of system testing using ISO 25010 which consists of 8 aspects of testing. The type of research used in this study is Research and Development (R&D), with the System Development Life Cycle (SDLC) development model. Data collection techniques using observation, interviews, and questionnaires. The results of this study, namely: (1) Functional suitability on the system that has been made is 100%